Kontribusi Gerakan Lembaga Dakwah Islam Indonesia (LDII) dalam Penguatan Nilai-Nilai Kebangsaan di Indonesia: Kajian Historis dan Sosiologis - Yunus Sulthonul Khakim (Medan Resource Center, 2024)
The Lembaga Dakwah Islam Indonesia (LDII) is one of the Islamic socio-religious organizations that has played an important role in fostering religious values, nationalism, and social development in Indonesia. Despite various dynamics throughout its historical development, LDII has continued to contribute to strengthening national character and supporting national progress. This study aims to analyze the historical development of LDII and examine its contributions to advancing the nation and state. The research employs a historical method consisting of topic selection, heuristics, source criticism, interpretation, and historiography. The findings reveal that LDII was founded by K.H. Nur Hasan Al-Ubaidah Lubis and has developed into an integral part of Indonesian society. In its organizational movement, LDII consistently promotes the values of Pancasila, national insight, and civic responsibility among its members. Furthermore, LDII contributes to national development through the implementation of eight flagship programs covering religious, educational, social, economic, and environmental sectors. These findings imply that religious organizations such as LDII can serve as strategic partners in strengthening national resilience, fostering social cohesion, and supporting sustainable national development in Indonesia.